2014
DOI: 10.1149/2.0451410jes
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Ni-Cu Thin Film Material Library Using Pulsed Electrodeposition

Abstract: A thin film composition gradient library of the Ni-Cu alloy system is generated through an electrodeposition technique using a complexing citrate electrolyte bath in a modified Hull cell. Energy dispersive X-ray spectroscopy, scanning electron microscopy and automated X-ray diffraction are performed to assess composition, surface morphology, and crystallographic structure of the deposited film as a function of the lateral position on the materials library. The results confirmed deposition of single phase polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Srinivas et al. fabricated copper–nickel material libraries in a Hull cell via pulsed electrodeposition. Using a similar approach, cobalt–nickel material libraries have been prepared galvanostatically from chloride and sulfate‐based electrolyte solutions ().…”
Section: Introductionmentioning
confidence: 99%
“…Srinivas et al. fabricated copper–nickel material libraries in a Hull cell via pulsed electrodeposition. Using a similar approach, cobalt–nickel material libraries have been prepared galvanostatically from chloride and sulfate‐based electrolyte solutions ().…”
Section: Introductionmentioning
confidence: 99%
“…. The complete experimental and characterization details include composition and conditions of the electrolyte, modified Hull cell with the electrodes’ geometry and dimensions, applied pulse parameters, structural, morphological, and chemical composition of the fabricated samples are found elsewhere . Nevertheless, the deposition experiments are performed at 2 mA cm −2 for 180 min.…”
Section: Methodsmentioning
confidence: 99%
“…For example electrodeposited Cu‐Sn material libraries for Li ion batteries applications . More recently, increased interest is found in using a modified Hull cell to fabricate various alloy material libraries . To understand the mechanism of electrodeposition of alloy material libraries in modified Hull cell, an overview of theoretical models is essential.…”
Section: Introductionmentioning
confidence: 99%
“…They modified the Hull cell to improve the compositional variation, and achieved and described how the current density gradient establishing between the inclined electrodes in combination with mass‐transfer limitation for copper during electroplating results in a material library. More recently, Srinivas et al reported on the preparation of Ni–Cu material libraries by pulse‐plating , . Moreover, Co–Ni material libraries were prepared with an addition of citrate or glycine to the electrolyte bath and without bath additives .…”
Section: Introductionmentioning
confidence: 99%